2022
DOI: 10.1371/journal.pone.0275637
|View full text |Cite
|
Sign up to set email alerts
|

Association of childhood trauma, and resilience, with quality of life in patients seeking treatment at a psychiatry outpatient: A cross-sectional study from Nepal

Abstract: Quality of life is defined by the World Health Organization as "Individuals’ perception of their position in life in the context of the culture and value systems in which they live and in relation to their goals, expectations, standards and concerns". It is a comprehensive measure of health outcome after trauma. Childhood maltreatment is a determinant of poor mental health and quality of life. Resilience, however, is supposed to be protective. Our aim is to examine childhood trauma and resilience in patients v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…A large-scale, cross-sectional study of college students in China revealed a relationship between childhood sexual abuse, post-traumatic stress disorder (PTSD), and other psychiatric symptoms (Jin et al, 2022). A descriptive cross-sectional study conducted in Nepal revealed that emotional neglect during childhood and depression were independent predictors of poor quality of life (Dhungana et al, 2022).…”
Section: Health and The Social Environmentmentioning
confidence: 99%
“…A large-scale, cross-sectional study of college students in China revealed a relationship between childhood sexual abuse, post-traumatic stress disorder (PTSD), and other psychiatric symptoms (Jin et al, 2022). A descriptive cross-sectional study conducted in Nepal revealed that emotional neglect during childhood and depression were independent predictors of poor quality of life (Dhungana et al, 2022).…”
Section: Health and The Social Environmentmentioning
confidence: 99%